Diversity and Evolution of Mineralized Skeletal Tissues in Chondrichthyans - Berio, Fidji; Broyon, Morgane; Enault, Sébastien; Pirot, Nelly; López-Romero, Faviel A.; Debiais-Thibaud, Mélanie (Frontiers in Ecology and Evolution, 2021)
The diversity of skeletal tissues in extant vertebrates includes mineralised and unmineralised structures made of bone, cartilage, or tissues of intermediate nature. This variability, together with the diverse nature of skeletal tissues in fossil species question the origin of skeletonisation in early vertebrates. In particular, the study of skeletal tissues in cartilaginous fishes is currently mostly restrained to tessellated cartilage, a derived form of mineralised cartilage that evolved at the origin of this group. In this work, we describe the architectural and histological diversity of neural arch mineralisation in cartilaginous fishes. The observed variations in the architecture include tessellated cartilage, with or without more massive sites of mineralisation, and continuously mineralised neural arches devoid of tesserae. The histology of these various architectures always includes globular mineralisation that takes place in the cartilaginous matrix. In many instances, the mineralised structures also include a fibrous component that seems to emerge from the perichondrium and they may display intermediate features, ranging from partly cartilaginous to mostly fibrous matrix, similar to fibrocartilage. Among these perichondrial mineralised tissues is also found, in few species, a lamellar arrangement of the mineralised extracellular matrix. The evolution of the mineralised tissues in cartilaginous fishes is discussed in light of current knowledge of their phylogenetic relationships.